KEBIJAKAN HUKUM PIDANA BAGI PENGEDAR NARKOTIKA PADA TINGKAT PENYIDIK DI WILAYAH HUKUM SUMATERA UTARA (STUDI KASUS KEPOLISIAN DAERAH SUMATERA UTARA) - Rio Nababan; Madiasa Ablisar; Mahmul Siregar; Mahmud Mulyadi (JURNAL JUSTIQA, 2020)
Sumatera Utara as one of the entrances to the Asian economic trade, which is going to the Continent of Australia. Therefore Indonesia, especially North Sumatra, is a very strategic city for Narcotics trade routes in Asia. Data from the Sumatera Utara Regional Narcotics Directorate has increased Narcotics cases both as users or as narcotics dealers every year, from 2015 there were 4,319 cases and in 2016 there were 5,460 Narcotics Cases and in 2017 there were 5,897 cases. In this study using a juridical empirical approach and the nature of descriptive analytical research. The problem in this study is how the criminal law policy for narcotics dealers at the investigator level in the jurisdiction of North Sumatra Regional Police and what are the Constraints in criminal law policy for eradicating Narcotics dealers at the investigator level in the North Sumatra Regional Police as well as how future policy towards legal policy criminal for Narcotics dealers at the investigator level in the jurisdiction of the North Sumatra Regional Police. The results of this study provide a conclusion that in terms of legislation it is necessary to establish a law or umbrella in implementing Undercover Buy and Phone intercept so that investigators in carrying out their duties do not hesitate, in terms of law enforcement officials need to push the Agency Diklat Polri to conduct training for North Sumatra Regional Police Narcotics investigators as well as from the legal culture aspect the pelu increases public awareness very low to assist the police in matters of complaints or reporting on narcotics crimes in the North Sumatra Regional Police.